Sentinel lymph node biopsy in cutaneous melanoma - Oliveira,Andrea Fernandes de (2007)
PURPOSE: To assess the importance of sentinel lymph node biopsy in patients with cutaneous melanoma. METHODS: Ninety consecutive non-randomized patients with stages I and II melanoma who underwent sentinel lymph node biopsy were followed up prospectively for six years. RESULTS: Patients were followed up for a mean period of 30 months. Their mean age was 53.3 years, ranging from 12 to 83 years. Thirty patients were male (37.5%) and 50, female (62.5%). Sentinel lymph node was positive in 32.5% and negative in 67.5%. It was found that the thicker the tumor, the greater the incidence of positive sentinel lymph nodes. In the group of patients with positive sentinel lymph nodes, recurrence occurred in 43.5%, but in those with negative sentinel lymph nodes, in only 7%, what points out to the association of tumor recurrence and positive sentinel lymph nodes. There were no major postoperative complications. CONCLUSION: Sentinel lymph node biopsy was demonstrated to be a safe method for selecting patients who need therapeutic lymphadenectomy.